2018
DOI: 10.17159/2078-5151/2018/v56n3a2486
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of disease and outcome of primary amputation for diabetic foot sepsis in rural KwaZulu-Natal

Abstract: Background: Primary amputation (stump closure) for diabetic foot sepsis is perceived to have a higher re-amputation rate due to stump sepsis. A guillotine amputation with elective stump closure is widely practised due to the lower risk of stump sepsis and re-amputation. Aims: To provide an epidemiological analysis of the spectrum of disease and outcomes of primary amputation for diabetic foot sepsis in a regional rural hospital. Methods: A prospective cohort study of 100 patients who underwent surgery for diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Although it has high diagnostic value, some patients have unclear local infection symptoms and cannot quantitatively analyse the risk of infection, and its application is limited 12 . Related studies have pointed out that various inflammatory indicators are related to the occurrence and development of infections in the body, and can be used to early evaluate the risk of infection 13 . This study retrospectively studied the clinical data of DFU and explored the risk factors related to DFU amputation, aiming to provide theoretical basis for the prevention and treatment of DFU 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has high diagnostic value, some patients have unclear local infection symptoms and cannot quantitatively analyse the risk of infection, and its application is limited 12 . Related studies have pointed out that various inflammatory indicators are related to the occurrence and development of infections in the body, and can be used to early evaluate the risk of infection 13 . This study retrospectively studied the clinical data of DFU and explored the risk factors related to DFU amputation, aiming to provide theoretical basis for the prevention and treatment of DFU 14 .…”
Section: Discussionmentioning
confidence: 99%
“…12 Related studies have pointed out that various inflammatory indicators are related to the occurrence and development of infections in the body, and can be used to early evaluate the risk of infection. 13 This study retrospectively studied the clinical data of DFU and explored the risk factors related to DFU amputation, aiming to provide theoretical basis for the prevention and treatment of DFU. 14 Binary logistic regression analysis showed that the independent risk factors for DFU amputation include elevated CRP, elevated WBC count, elevated NLR and elevated Wagner grading.…”
Section: Discussionmentioning
confidence: 99%
“…A study from the rural town of Newcastle in the northern part of the province identified 100 patients requiring LLA for diabetes over a 4-year period. [19]. These figures are very much in keeping with our own.…”
Section: Discussionsupporting
confidence: 87%
“…25,26 There is variability in the prevalence of amputation levels in the lower extremity among different studies. BKAs predominated in this series, an observation made by other local 21 and international studies. 17,18,24 Other studies, however, have shown a predominance of AKAs.…”
Section: Discussionsupporting
confidence: 76%
“…7,8,[17][18][19] The majority of diabetic-related amputations are preceded by foot ulcers which act as a portal for infection leading to sepsis or gangrene that may require amputation. 21,22 This is further compounded in diabetics by peripheral vasculopathy and neuropathy which also contribute to the risk of amputation. 23 There is geographical variation in amputation rates worldwide.…”
Section: Discussionmentioning
confidence: 99%